Biofeedback-Guided Voice Therapy for Pediatric Habitual Dysphonia: Evidence, Mechanisms, and Clinical Implications (Cuestiones de Fisioterapia, 2024)
Background: Habitual dysphonia is one of the most frequently encountered voice disorders in pediatric populations and is commonly associated with chronic vocal misuse, phonotraumatic behaviors, and functional alterations in phonatory patterns. Children with habitual dysphonia often present with hoarseness, vocal fatigue, reduced vocal endurance, and altered pitch or loudness characteristics. If left untreated, these abnormal vocal behaviors may lead to structural changes in the vocal folds such as vocal nodules and may significantly